1983
DOI: 10.1093/ptj/63.6.934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vibration on Tactile Sensitivity

Abstract: Tactile hypersensitivity is a common sequela of traumatic hand injury. Vibration is used clinically to reduce this hypersensitivity. The purpose of this study was to determine if vibration has an effect on tactile threshold and if so to determine the duration of that effect. Mean tactile thresholds were determined for 24 healthy adults by means of a pressure aesthesiometer. The experimental group (6 men, 6 women) received 10 minutes of vibration. Mean tactile thresholds were redetermined at the end of the 10-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Outcome measures included force plate measurements for postural sway, postural sway via motion analysis, and temporal and spatial gait parameters via motion analysis (Miranda et al, 2016;Stephen et al, 2012). All of these studies indicated that subthreshold noise improved balance control, tactile sensation (Dettmer, Pourmoghaddam, Lee, & Layne, 2016;Hochreiter, Jewell, Barber, & Browne, 1983), and vibration sensation (Bagherzadeh Cham et al, 2016). The benefits of stochastic resonance have also improved balance in other populations such as Cerebral Palsy(CP).…”
Section: Introductionmentioning
confidence: 99%
“…Outcome measures included force plate measurements for postural sway, postural sway via motion analysis, and temporal and spatial gait parameters via motion analysis (Miranda et al, 2016;Stephen et al, 2012). All of these studies indicated that subthreshold noise improved balance control, tactile sensation (Dettmer, Pourmoghaddam, Lee, & Layne, 2016;Hochreiter, Jewell, Barber, & Browne, 1983), and vibration sensation (Bagherzadeh Cham et al, 2016). The benefits of stochastic resonance have also improved balance in other populations such as Cerebral Palsy(CP).…”
Section: Introductionmentioning
confidence: 99%